Analysis of Students' Understanding Level of Character Education at RA Miftahul Jannah Medan - Salsabila Erliani, T. Darmansah, Nadia Sabrina Siregar, Aliyyah Putri Az Zahra, Nurul Anjani Daulay (Pusdikra-Publishing.com, 2023)
Character education in early childhood plays a crucial role in forming a moral basis and positive behavior. This article reviews important efforts in developing children's character through early education. This article discusses character education strategies that involve collaboration between families, schools and communities. Emphasizing values ??such as cooperation, responsibility, and empathy, character education creates an environment that supports children's moral development from an early age. Through creative and interactive learning methods, children are invited to understand moral concepts practically in everyday life. In addition, the play approach is combined with moral values ??to create a fun and meaningful learning experience. In this context, the role of teachers and parents as role models is very important. The importance of providing moral understanding at an early age is to form a strong foundation of character that will guide children towards a meaningful and responsible life. Thus, this article summarizes the urgency of character education in early childhood as a valuable investment in building a better society.